Positive solutions of a class of reaction–diffusion equations in spatially heterogeneous environment. (November 2020) - Li, Shanbing; Dong, Yaying
Abstract: In this paper, we study the existence of positive solutions for a class of reaction–diffusion equations in spatially heterogeneous environment. We also determine the asymptotic profiles of positive solutions when some parameter goes to zero. Our analytical results suggest that the spatial heterogeneity has obvious influence on the positive solutions.